Development and Characterization of Methotrexate Bearing Emulsomes for Management of Skin Cancer (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The present study is aimed to manage skin cancer via topical route, because of conventional chemotherapy having lots of drawbacks like drugs introduced into the body through an injectable route thus drugs are distributed between normal cell and cancerous cell than its leading to unaccepted side effects and requires high dose of drug. In this paper, main focus onto overcome these drawbacks, emulsomes were developed loaded with methotrexate bio-active agent. A 32 factorial design approach was employed firstly for the formulation development of emulsomes for different concentration of lipid content which was phosphatidyl choline, cholesterol and solid core lipid. Developed methotrexate loaded emulsomes were characterized for particle size, polydispersity index, zeta potential and entrapment efficiency and results revealed 127.21 ± 1.11 nm, 0.216, -24.21 ± 1.09 mv, and 81.37 ± 0.8%, respectively. Thus optimized lipid content was further used for optimization of type and concentration of surfactants9 and sonication time. Hence 18 formulations of emulsomes were developed and characterized for particle size, polydispersity index, zeta potential and entrapment efficiency and result 126 ± 1.09 nm, 0.215, -24.81 ± 1.19 mv, and 85.17 ± 0.3%, respectively. These formulations were tested for their in-vitro drug release studies and release data show the value of t½ for formulations EM4F11, EM4F18 and EM4F8 was more than 12 h and they were retarded drug release up to 85% till 24 h to get better-sustained drug release profile. Then stability study was performed for formulation EM4F11 at 2 ± 2°C, 25 ± 2°C and 60% RH and 40 ± 2°C and 75% RH and data identified that the formulations stored at temperature 25 ± 2°C and 60% RH and it was less than 2% degradation at the end of six months. Hence developed emulsomes formulation might represent a promising system for improving the bioavailability of lipophilic drugs. Moreover, emulsomes produce sustained drug release, which is beneficial clinically. Thus the presented system adds additional benefits to the well-known opportunities to the conventional delivery system and is helpful in minimizing the side effects of anti-cancerous drugs and well suited for the management of skin ailment.